1997
DOI: 10.1038/sj.onc.1200992
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of NF-κB activity and NF-κB p65 subunit expression by ras and polyoma middle T oncogenes in human colonic Caco-2 cells

Abstract: The products of ras and src proto-oncogenes are frequently activated in a constitutive state in human colorectal cancer. In this study we attempted to establish whether the tumorigenic progression induced by oncogenic activation of p21 ras or pp60 c-src in human colonic cells is associated with alterations of the activity and expression of nuclear factor kB (NF-kB), a transcription factor suspected to participate in the development of cancer. To this end, we used Caco-2 cells made highly tumorigenic by transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…It is therefore possible that, beside the PKC-mediated e ect, ras additionally alters Cdx-2 gene transcription through PKC-independent pathway(s). In this case, we can exclude the P13K (Phosphatidyl-Inositol-3 kinase) and NF-kB pathways, because the treatment of Caco-2T/MT/MT cells by LY294002 to inhibit P13K activity or by TNFa to restore the NF-kB activity altered by Ha-ras (Cadoret et al, 1997), are ine ective on the expression of Cdx-2 downregulated by oncogenic ras; we also rule out the JNK/SAPK pathway (Jun Nterminal kinase/Stress-Activated-Protein kinase) because JNK activity is unchanged in ras-activated Caco-2T/MT cells compared to control cells (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore possible that, beside the PKC-mediated e ect, ras additionally alters Cdx-2 gene transcription through PKC-independent pathway(s). In this case, we can exclude the P13K (Phosphatidyl-Inositol-3 kinase) and NF-kB pathways, because the treatment of Caco-2T/MT/MT cells by LY294002 to inhibit P13K activity or by TNFa to restore the NF-kB activity altered by Ha-ras (Cadoret et al, 1997), are ine ective on the expression of Cdx-2 downregulated by oncogenic ras; we also rule out the JNK/SAPK pathway (Jun Nterminal kinase/Stress-Activated-Protein kinase) because JNK activity is unchanged in ras-activated Caco-2T/MT cells compared to control cells (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…EMSA was performed as previously described (Cadoret et al, 1997), with the labelled double-stranded Cdx2-AP1 oligonucleotide (d CGA TTGGTGTCTGTGTCAT-TAC TA ATAGA / dAGACTCTAT TAGTA ATGACACA-GACACCA). Competition with DNA used a 30-fold excess of unlabelled oligonucleotide; the DNA competitors were Cdx2-AP1, Std-AP1 (dCGCTTGATGAGTCAGCCG-GAA/dTTCCG-GCTGACTCATCAAGCG) containing a consensus AP-1 binding site, or OCT-1 (dTGTCGAATG-CAAATCACTAGAA/dTTCTAGTGATTTGCATTCGA-CA) containing an OCT-1 site.…”
Section: Electromobility Shift Assays (Emsa)mentioning
confidence: 99%
“…So far, only a few studies have reported on the regulation of p65 expression at the posttranscriptional level (43,44). Although the ubiquitously encoded housekeeping p65 gene does not contain NF-kB binding motifs in its promoter region (45), the p65 transcript has three AU-rich elements in the 39 untranslated region, which would make the gene susceptible to regulation by RNAstabilizing HuR protein.…”
Section: Discussionmentioning
confidence: 99%
“…Membranes were hybridized (3 h at 65°C) in Rapid-Hyb buffer (Amersham Pharmacia Biotech) to a random-primed labeled cDNA probe specific for TRAF2, c-IAP1, c-IAP2, or Mn-SOD and subsequently to a labeled human elongation factor 1 probe as a control for RNA loading. Membranes were then washed to high stringency as described (24). Signals were quantified and normalized by differential densitometric scanning of the specific bands versus the human elongation factor 1 band.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA (20 g) or poly(A) ϩ RNA (2.5 g) was electrophoresed and transferred to Hybond-N ϩ nylon membranes (Amersham Pharmacia Biotech) as described (24). Membranes were hybridized (3 h at 65°C) in Rapid-Hyb buffer (Amersham Pharmacia Biotech) to a random-primed labeled cDNA probe specific for TRAF2, c-IAP1, c-IAP2, or Mn-SOD and subsequently to a labeled human elongation factor 1 probe as a control for RNA loading.…”
Section: Methodsmentioning
confidence: 99%